Solution Idea of MSMEs Based on Cluster in East Java During the Covid-19 Crisis: Can Survive or Not? - Shella Elly Sritrsiniawati (East Java Economic Journal, 2022)
Based on history, MSMEs were able to survive the Asian economic crisis. With the COVID-19 pandemic crisis that is currently happening in the world and in the State of Indonesia, especially East Java, it is also affected. This study will explain whether MSMEs will continue to be hero in restoring the economic conditions of the East Java Region. Solutions and strategic ideas that may be carried out by East Java MSMEs in order to be able to survive on COVID-19 pandemic, one of which is a cluster based approach. Solution ideas related to the development and growth of MSMEs clusters in East Java need to be supported by innovation business based on incubation proces. Activities with incubators system for MSMEs that are still premature. Strategic ideas in the context of sustainable economic recovery due to the pandemic depend on the ability of East Java MSMEs to increase innovation. It was concluded that East Java MSMEs could implement a cluster based system to strengthen the network and supply of resources needed in the business. By forming clusters and implementing a marketing strategy expansion, geographic coverage, wide distribution and cost products efficiency strategies. So, it can be maintaining production and increasing productivity to optimization resource channels as to expand domestic and international markets.